Analisis Peran Transportasi Sungai (Ketek) Pada Perekonomian Masyarakat Desa Rantau Rasau Kabupaten Tanjung Jabung Timur - Al Ikhsan; Maulana Yusuf; Bella arisha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Rantau Rasau Village, which is one of the villages in Berbak sub-district, Tanjung Jabung Timur district. To get to Rantau Rasau village we have to use river transportation services in the form of ketek (a type of large boat equipped with a robbins engine), this water transportation. It is the only access to Rantau Rasau village because there is no land road to the village. This thesis aims to determine the role of air transportation in the economy of the people of Rantau Rasau village, East Tanjung Jabung district, to find out what obstacles exist in the use of this transportation.This research is qualitative research with descriptive methods, data collection techniques using interviews, observation and documentation. The results of the research show that the role of air transportation in the economy of the Rantau Rasau village community, East Tanjung Jabung Regency, includes mobility for people in and out of the village and also as a bridge for all economic activities of the Rantau Rasau village community. Obstacles in using this transportation service are tides and unpredictable weather conditions. Keywords: Water Transportation, Community Economy, Watershed